Particle residence time distributions in a vortex-based solar particle receiver-reactor: The influence of receiver tilt angle. (15th September 2019) - Davis, Dominic; Troiano, Maurizio; Chinnici, Alfonso; Saw, Woei L.; Lau, Timothy; Solimene, Roberto; Salatino, Piero; Nathan, Graham J.
Highlights: Direct measurements of influence of receiver tilt angle on particle residence time. Vortex-based solar particle receiver investigated with tilt angles spanning 180°. Tilt angle influence is significant for large particles, weak for small particles. Preferable to operate tower-mounted receivers with smaller particles. Residence time behaviour modelled with combination of classical ideal flow reactors. Abstract: We present the first experimental assessment of the influence of receiver tilt angle on the particle residence time distribution (RTD) of a two-phase solar particle receiver. The tracer pulse response method is used to measure the particle RTD within a laboratory-scale vortex-based solar particle receiver, with the particle phase itself used as the tracer. The experimental parameters of particle size, transporting gas inlet velocity and a range of receiver tilt angles – spanning 180° from vertically upward to downward facing – were systematically varied to determine the influence of key controlling parameters on the particle RTD within the receiver. It was found that the Stokes number of the two-phase flow evaluated at the receiver outlet, Skout, has a controlling influence on the residence time and that the influence of the receiver tilt angle is significant for large particles ( Skout > 10) but weak for small particles ( Skout 1). This implies that it is preferable to operate tower-mounted systems (i.e. with downward facing receiver tilt angles) with Skout 1. Furthermore, a preliminary scale-up assessment suggests that the influence of tilt angle on the residence time of particles 200 µm and smaller will be insignificant for a nominal 50 MW-scale receiver, which will provide flexibility in the design of industrial-scale devices. Finally, the residence time behaviour for the range of tilt angles assessed can be well described by an analytical compartment model consisting of a small plug flow reactor, followed by two continuously-stirred tank reactors in parallel with a second plug flow reactor.